Characterization of sewage sludge for sustainable urban environments: assessing heavy metal enrichment, thermal decomposition, and pyrolysis behavior/ Mohd Syazwan Mohd Ghazali and Syed Shatir A. Syed-Hassan - Mohd Ghazali, Mohd Syazwan; A. Syed Hassan, Syed Shatir (Universiti Teknologi MARA, Perak, 2024)
Rapid urbanisation and population growth have led to a surge in sewage sludge (SS) generation, posing environmental challenges due to its complex composition, particularly heavy metal content. This study investigates heavy metal analysis, thermal decomposition behaviour, and slow pyrolysis of SS to address these concerns. SS samples were collected from a sewage treatment plant and analysed for heavy metals using ICP-OES. Thermogravimetric analysis (TGA) clarified thermal decomposition behaviour, while slow pyrolysis experiments at varying temperatures provided insights into product yields. Results revealed significant concentrations of heavy metals and other elements in SS, with pyrolysis temperatures between 450°C and 600°C ensuring complete conversion of volatile matter. Slow pyrolysis predominantly yielded biochar, indicating limited suitability for bio-oil production. Additionally, pyrolysis enriched biochar with heavy metals while decreasing cobalt concentration, highlighting complex mechanisms in heavy metal redistribution. This research contributes to understanding heavy metal behaviour and thermal conversion dynamics in sewage sludge, informing sustainable waste management strategies for mitigating environmental impacts.